Pengukuran Kinerja Rantai Pasok Dengan Model Supply Chain Operations Reference (SCOR) dan Metode Perbandingan Berpasangan - Liputra, David Try; Santoso, Santoso; Susanto, Nadya Ariella (Jurnal Rekayasa Sistem Industri, 2018)
The rapid development of the industrial world has resulted in increasingly tight competition among companies. This condition shows the importance of improving performance, not only in a company but also other parties in the related supply chain, in order to compete with other companies or supply chains. The good performance of a supply chain will certainly increase the customers satisfaction. Therefore, performance measurement needs to be carried out so that a supply chain can find out how well it currently performing is and keep improving it. This study will discuss about the application of the supply chain operations reference (SCOR) model and the pairwise comparison method for the supply chain performance measurement of a product packaging companyÂ Keywords: supply chain, performance measurement, SCOR, pairwise comparison